Reduplication as a word-formation process in the Jamee Language: A variety of Minang spoken in South Aceh - Zulfadli A. Aziz; Vivi Nolikasari (Studies in English Language and Education, 2020)
One of the processes of word formation is reduplication which words or morphemes are repeated. This study focuses on reduplication in Jamee language. This descriptive qualitative study aims at finding out forms of reduplication and the meaning contained in the reduplication in Jamee. The data were collected through ethnographic interview by recording ten native speakers of the Jamee language who live in Labuhanhaji sub-district, South Aceh. They were chosen through purposive sampling. A total of 261 reduplication words were obtained during the interviews, and they were analysed using three stages; data reduction, data display and data verification. Based on the results of data analysis, it was found that there are four types of reduplication in the Jamee language: full reduplication, partial reduplication, lexicalized reduplication, and affixed reduplication. The study also shows that reduplication in Jamee language can be in the forms of verbs, nouns, adjectives, adverbs, and pronominals. Despite previous studies show that there is no infix in the Jamee language, hence it does occur in this study even though it is rarely used in this language. It is assumed that it may have come into the language through the borrowing from Bahasa Indonesia.